The Potency of Halim Perdanakusuma Airport Development as Commercial Airport - Miming Miharja; Dwitami Puspaningrum (Institut Teknologi Bandung, 2017)
AbstractNowadays, Halim Perdanakusuma Airport plays a role in facilitating commercial and military flight activities. In the commercial flight segment, the role of Halim Perdanakusuma airport is expected to reduce the load of Soekarno-Hatta International Airport in serving the ever increasing flight volume. As part of this concern, this article analyzes the potency of Halim Perdanakusuma Aiport to respond the growing demand of commercial flight based on land side and air side development potential factors. The potency of development from land side is based on the space availability to meet the standard of passenger service facilities, whereas the air side is based on the airport runway capacity in accommodating the number of aircraft take-off and landing activities according to their types as well as loading capacities. The need for airport development is based on the standard of space needs for each passenger during the peak time. Analysis result shows that the most critical constraint is coming from land sidedue to space limitation for the development of various facilities required to fulfil the service standard, which available only for up to 2,750,369 total passengers per year. Meanwhile, there is no significant constraint for airport development from the air side point of view.AbstrakSaat ini, Bandara Halim Perdanakusuma berperan dalam memfasilitasi kegiatan penerbangan komersil dan militer. Pada segmen penerbangan komersial, peran Bandara Halim Perdanakusuma diharapkan dapat mengurangi beban Bandara Internasional Soekarno-Hatta dalam melayani volume penerbangan komersial yang semakin meningkat. Fokus tulisan ini adalah menganalisis potensi Bandara Halim Perdanakusuma dalam merespon tumbuhnya permintaan dari penerbangan komersial berdasarkan faktor-faktor potensi pengembangan sisi darat dan sisi udara. Potensi pengembanga dari sisi darat didasarkan pada ketersediaan ruang untuk memenuhi standar fasilitas pelayanan penumpang, sedangkan dari sisi udara berdasarkan pada potensi pengembangan kapasitas landasan pacu bandara dalam melayani aktifitas take-off dan pendaratan pesawat sesuai dengan jenis dan kapasitas angkutnya. Kebutuhan untuk pengembangan bandar udara didasarkan pada standar kebutuhan ruang untuk penumpang pada waktu puncak. Hasil analisis menunjukkan bahwa kendala pengembangan bandara terutama datang dari sisi darat yang disebabkan oleh keterbatasan ruang bagi pengembangan berbagai fasilitas yang diperlukan untuk memenuhi standar pelayanan, yang hanya tersedia untuk melayani 2.750.369 total penumpang per tahun. Sementara itu, tidak terdapat kendala yang signikan untuk pengembangan bandara dari sisi udara.